EFEKTIVITAS BERMAIN MEWARNAI TERHADAP PENURUNAN TINGKAT STRES PADA MURID FULL DAY SCHOOL - Fitriatul Masruroh; Luluk Masluchah; Herrien Triwahyuni (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to examine the effectiveness of playing coloring pictures against reducing stress levels in full day school students of SD Islam Roushon Fikr Jombang. The hypothesis proposed is that there is an effect of playing coloring pictures on decreasing stress levels in full day school pupils. The population in this study was grade VI students of Roushon Fikr Islamic Elementary School aged 11-12 years. The sample taken was a sixth-grader of 52 students with purposive random sampling technique, consisting of 26 students as a control group, and 26 students as an experimental group. The free variable in this study is playing coloring images, while the dependent variable is the level of stress revealed with the scale. Data analysis used T-test analysis between groups. The results of the t-test between A1-A2 found that t = 9.664 with p = 0.000 (p < 0.01), this shows that there is a very significant difference in terms of stress between students who do not participate in drawing coloring games and students who follow drawing coloring games. The stress of pupils who follow coloring games (A2) is lower than that of pupils who do not participate in coloring games (A1). These results suggest that the hypothesis proposed in the study is accepted.